2014
DOI: 10.1007/s12012-014-9252-4
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Cardiomyopathy: Pathophysiologic Insights

Abstract: Alcoholic cardiomyopathy is a specific heart muscle disease found in individuals with a history of long-term heavy alcohol consumption. Alcoholic cardiomyopathy is associated with a number of adverse histological, cellular, and structural changes within the myocardium. Several mechanisms are implicated in mediating the adverse effects of ethanol, including the generation of oxidative stress, apoptotic cell death, impaired mitochondrial bioenergetics/stress, derangements in fatty acid metabolism and transport, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
136
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 93 publications
(165 reference statements)
1
136
0
4
Order By: Relevance
“…Alcoholic cardiomyopathy (ACM), which is characterized by cardiac hypertrophy and compromised myocardial contractility associated with chronic alcohol consumption, has long been recognized as one of the major toxicological effects of ethanol in the cardiovascular system (Guzzo-Merello et al 2015;Piano and Phillips 2014). The link between alcoholism and left ventricle dysfunction has been reported in heart disease (Guzzo-Merello et al 2014;Guzzo-Merello et al 2015;Piano and Phillips 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic cardiomyopathy (ACM), which is characterized by cardiac hypertrophy and compromised myocardial contractility associated with chronic alcohol consumption, has long been recognized as one of the major toxicological effects of ethanol in the cardiovascular system (Guzzo-Merello et al 2015;Piano and Phillips 2014). The link between alcoholism and left ventricle dysfunction has been reported in heart disease (Guzzo-Merello et al 2014;Guzzo-Merello et al 2015;Piano and Phillips 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The link between alcoholism and left ventricle dysfunction has been reported in heart disease (Guzzo-Merello et al 2014;Guzzo-Merello et al 2015;Piano and Phillips 2014). For instance, the incidence of congestive cardiomyopathy is greatly enhanced in populations of patients involved with ethanol addiction (Fernandez-Sola 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnosis is generally made in heavy drinkers with myocardial dysfunction in the absence of other identified causes (5). Ethanol intake ≥24 g per day in females and ≥36 g per day in males has been found to cause hypertension; therefore, hypertension frequently contributes to LV dysfunction in cases of cardiomyopathy (6).…”
Section: Discussionmentioning
confidence: 99%
“…ACM is a cardiac disease found in individuals exposed to high levels of alcohol consumption for a long period, which can lead to cardiac dysfunctions and heart failure [21,22]. Lazarevic et al [23 ]have found that alcoholics (with alcohol consumption >90 g/day, ≥4 days/week) have a significant increase in LV diameter and volume, but did not observe any differences in systolic function.…”
Section: Discussionmentioning
confidence: 99%